Does Tax Plays an Important Role among E-commerce Businesses in Malaysia? - Morni Hayati Jaafar Sidik (Journal of Information Technology Management)
The E-commerce has been grown rapidly with the rise in the number of business entities. The expansion of e-commerce businesses, however, has created challenges to the tax authorities around the world. Due to the way in which e-commerce is being carry out, it may provide tax planning opportunities. This study aims to explore whether businesses that conducted e-commerce in Malaysia has the intention to do tax planning. Interviews were conducted with e-commerce business administrators. Result indicates that tax issues is not the main motivations for companies to do e-commerce. This indicates that other factors are more important for e-commerce businesses to consider in their planning stage